Law, Foreign Policy, and the East-West Détente - McWhinney, Edward (Book collections on Project MUSE., 2018)
This book has its roots in a conference on Law and World Affairs held in the Faculty of Law, University of Toronto, in 1964. Specialists representing government, universities and the press met to discuss the response of the West in general, and of Canada in particular, to recent far-reaching changes in Soviet external relations.